A comparison of decision tree data mining algorithms in SAS Enterprise miner and MS SQL Server Data Mining - Pondel, Maciej (Porównanie algorytmów drzew decyzyjnych w narzędziach SAS Enterprise Miner i MS SQL Server Data Mining, 2011)
Today’s business generates tremendous volumes of data. Most of the data are essential to provide operational processes. Though they are useful to support operational business processes they are also used for analysts. Analytical tools support processes on a higher – managing – level. This group of solutions is called Business Intelligence. A part of the business intelligence tools is data mining software. Various software producers develop their own Data Mining tools. Author of this paper has chosen two of them: Microsoft SQL Server 2008 and SAS Enterprise Miner and compared one of the available Data Mining methods
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 69-78
Keywords: data mining; SAS Enterprise Miner; MS SQL Server Data Mining; decision trees